Satellite InSAR Data: Reservoir Monitoring from Space - Ferretti A. Alessandro (Education tour series)
The purpose of this book is to educate and the text is written to complement a training class given by the author, on behalf of EAGE. The author and EAGE shall have neither liability nor responsibility to any person or entity with respect to any loss or damage caused, or alleged to have been caused, directly or indirectly, by the information contained in this book or from written or oral information provided in the complementary training classes. This book is designed to provide information on satellite InSAR and its applications. It includes reviews of existing published materials and contains references to a number of technical papers, expanded abstracts and text books. The intent has not been to produce a reprint of this material but instead to use it combined with the author's own experience to illustrate the practical use of satellite InSAR data. We recommend complementing the book by reading the referenced articles, to ensure readers have the best possible context and to help tailor the information to specific needs. Readers are urged to consult with experts on all aspects about which you are in doubt, prior to utilizing any of the ideas and concepts referred to in the textbook and the associated lecture. Every effort has been made to make this work as accurate as possible. However, there may be mistakes, both typographical and in content. Therefore, this text should be used only as a general guide and reference and not used as the ultimate source for commercial work.